2016
DOI: 10.3109/0284186x.2015.1114679
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic model for recurrent glioblastoma patients treated with bevacizumab and irinotecan

Abstract: Background Predictive markers and prognostic models are required in order to individualize treatment of recurrent glioblastoma (GBM) patients. Here, we sought to identify clinical factors able to predict response and survival in recurrent GBM patients treated with bevacizumab (BEV) and irinotecan. Material and methods A total of 219 recurrent GBM patients treated with BEV plus irinotecan according to a previously published treatment protocol were included in the initial population. Prognostic models were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…One explanatory factor is that DNA demethylation of the CEBP region in the AGT promoter may occur from the time of glioblastoma diagnosis to the time of glioblastoma recurrence as a result of continues AGT gene activation (Wang et al , 2014). Such stimulatory signals of AGT activation include the pro‐inflammatory cytokine interleukin‐6 and glucocorticosteroids (Wang et al , 2014), which both have been reported to predict poor outcome in bevacizumab‐treated cancer patients (Duerinck et al , 2015; Noonan et al , 2018; Urup et al , 2016a). In addition, the most prominent transcription factors known to induce angiotensinogen transcription are CEBP and STAT3 (Jain et al , 2007; Wang et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanatory factor is that DNA demethylation of the CEBP region in the AGT promoter may occur from the time of glioblastoma diagnosis to the time of glioblastoma recurrence as a result of continues AGT gene activation (Wang et al , 2014). Such stimulatory signals of AGT activation include the pro‐inflammatory cytokine interleukin‐6 and glucocorticosteroids (Wang et al , 2014), which both have been reported to predict poor outcome in bevacizumab‐treated cancer patients (Duerinck et al , 2015; Noonan et al , 2018; Urup et al , 2016a). In addition, the most prominent transcription factors known to induce angiotensinogen transcription are CEBP and STAT3 (Jain et al , 2007; Wang et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab in combination with chemotherapy has been shown to produce high response rates of approximately 30% in recurrent glioblastoma patients (Friedman et al , 2009; Urup et al , 2016a; Wick et al , 2017). Although this treatment has not proven active in the total population of recurrent glioblastoma patients (Taal et al , 2014; Wick et al , 2017), patients whom achieve response to bevacizumab combination therapy obtain clinical improvement and have prolonged survival (Henriksson et al , 2011; Huang et al , 2016; Jakobsen et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilized data sources were clinical parameters (n = 2) [19,32]; genomics (n = 2) [12,21]; MRI imaging (n = 4) [22,23,34,37]; combined clinical and genomics (n = 4) [13,16,27,28]; combined clinical and MRI imaging (n = 10) [14, 18, 20, 24, 25, 29-31, 35, 38]; combined clinical, MRI imaging, and genomics (n = 3) [15,26,36]; histopathology (n = 1) [33]; and combined clinical and pharmacokinetics (n = 1) [17]. Up to 2017, only two studies analyzed high-dimensional data sources (i.e., MRI or genomic information) in addition to clinical information [12,13].…”
Section: Type Of Inputmentioning
confidence: 99%
“…Overall survival was modeled as a continuous (n = 7) [15,17,26,28,30,35,38], binary (n = 11) [16,19,22,24,25,27,29,31,34,37,38], or time-to-event outcome (n = 11) [12-14, 18, 20, 21, 23, 32, 33, 36, 38]. In studies that defined survival as a binary outcome, survival was dichotomized into short and long survival at 6 [19], 12 [27,38], and 18 months [37], more or less than 400 days [31], as well as the median [29] and mean [25] overall survival in the training cohort.…”
Section: Outcome Definitionmentioning
confidence: 99%